MODERN AND LABORATORY DIAGNOSTIC METHODS FOR PATIENTS WITH HIV INFECTION (International journal of artificial intelligence, 2025)
This article examines the processes of identifying and monitoring patients infected with the human immunodeficiency virus (HIV) through modern diagnostic and laboratory methods. In particular, it discusses biochemical, immunological, and molecular methods used before, during, and after the initiation of antiretroviral therapy (ART) to evaluate its effectiveness, as well as the laboratory infrastructure implemented in Uzbekistan. The study methodology is based on a review of literature and analysis of national statistical data. The main section presents the stages of testing, various test systems, diagnostic strategies, and monitoring approaches in detail. The analysis and results section provides evidence on the current state of laboratory infrastructure and testing systems in Uzbekistan. The conclusion highlights the importance of modern diagnostic methods and outlines the existing challenges and recommendations for their implementation in clinical practice.